Calvin for the world the enduring relevance of his political, social, and economic theology - Rosario Rodríguez, Rubén 1970- (Baker Academic, a division of Baker Publishing Group, 2024)
"This book offers a creative engagement with the theological and political thought of John Calvin, showing that his theological legacy impacted the formation of the modern world, its worldview, and its social institutions."
Keywords: Calvin, Jean -- 1509-1564; Geschichte; Calvinismus; Calvin, Jean / 1509-1564 / Political and social views